A combined experimental and computational investigation on pyrene based D–π–A dyes. Issue 9 (12th February 2018) - Khamrang, Themmila; Velusamy, Marappan; Jaccob, Madhavan; Ramesh, Mohan; Kathiresan, Murugavel; Kathiravan, Arunkumar
Abstract : The geometry (twist vs. planar) of a dye is one of the most pivotal factors for determining intramolecular charge transfer (ICT), light harvesting and photovoltaic properties of dye-sensitized solar cells. Abstract : The geometry (twist vs. planar) of a dye is one of the most pivotal factors for determining intramolecular charge transfer (ICT), light harvesting and photovoltaic properties of dye-sensitized solar cells. In order to comprehend the role of dye geometry on the above properties, we have devised the pyrene based D–π–A dyes namely 2-cyano-3-(5-pyren-1-yl-furan-2-yl)-acrylic acid (PFCC ) and 2-cyano-3-(5-pyren-1-ylethynyl-furan-2-yl)-acrylic acid (PEFCC ). The synthesized pyrene dyes were well characterized by NMR and EI-MS spectrometry. In both the dyes, the donor (pyrene) and acceptor (cyanoacrylic acid) segments remained the same. The varied π-spacers were furan and ethynyl furan. The influences of the ethynyl spacer on the energy levels, light absorption, dynamics of excited states and photovoltaic properties of the DSCs were systematically investigated via theoretical calculations and spectroscopic measurements. UV-visible absorption spectral measurements indicated that the introduction of the ethynyl spacer enhances the molar absorptivity of a dye (PEFCC ) in the order of 2, but does not shift the absorption range, which is consistent with the results obtained from density functional theory (DFT) calculations. The theoretical analysis indicated that the charge transfer transition is mainly constituted of the HOMO to the LUMO that were found to be located on donor and acceptor segments, respectively, which is supportive for efficient charge separation and electron injection processes. TDDFT calculations highlighted that the LUMO of thePEFCC dye is more stabilized by the incorporation of the ethynyl group between the pyrene and furan moieties that aid to inject electrons efficiently into TiO2 thereby resulting in an enhanced power conversion efficiency of 2.47% when compared to thePFCC dye. Notably, the overall conversion efficiency of thePEFCC dye reached 60% with respect to that of an N719-based device (4.12%) fabricated under similar conditions. Transient absorption kinetic studies demonstrated that a slower charge recombination rate is an essential factor behind enhanced efficiencies inPEFCC based cells.